(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The implementation of training that runs effectively can be one of the important things in the development of human resources which has an impact on the increasing performance of employees at work. This research was conducted to determine how much influence job training has had on improving employee performance at PT. XYZ. The population in this study were all employees who worked at the Wharehouse Finish Good (FG), Wharehouse Raw Material & Packaging Material (RMPM), Quality Assurance (QA), and Production and Engineering at PT XZY, totaling 327 people. Meanwhile, the number of samples taken in this study, namely as many as 180 people with a sampling technique in the form of simple random sampling. In this study, the research method used is a causal associative type of research which aims to analyze the relationship between one variable and another. And for the data processing and analysis techniques used, namely in the form of simple linear regression analysis, the calculations use the SPSS for Windows Version 22.0 program. The research results obtained in this study indicate that an increase in employee performance can be influenced by the implementation of job training that is carried out effectively. Thus, it is concluded that the effectiveness of job training conducted by a company can improve the work results shown by its employees in relation to their working ability which is becoming more and more skilled.